دور إدارة العلاقات مع الزبائن في تنوع خدمات البنوك - جرورو, محمد الأمين (My University, 2022)
Through our study of the topic of the role of customer relationship management in the diversity and development of banking services, we By trying to get acquainted with the most important elements of the research, which is to identify the banking service as a new concept Enter into customer loyalty and the impact that the quality of banking services plays in increasing customer loyalty. In addition to the role of the role of customer relations in the bank For this purpose, we combined the theoretical study on the one hand and the field study on the one hand Other, where we dealt in our note the role of CRM in diversifying as well as developing banking services and how to retain the customer in addition to bringing new customers in the shortest time and at the lowest cost And to analyze the theoretical relationship between these two variables and try to bring it down at the level of the Bank of Agriculture and Rural Development and the Agency of Boukirat, Mostaganem Province.
دراسة حالة بنك الفلاحة والتنمية الريفية بوقيرات
Keywords: the role of customer relationship management - diversity - banking services - the Bank for Agriculture and Rural Development – service.